Italian marine Gastrotricha: VI. Seven new species of Macrodasyida - Hummon, William D.; Todaro, M. Antonio (Zootaxa, 2009)
Seven species new to science are described from Italian waters, some of which also occur along nearby coasts: Macrodasys acrosorus n. sp. and M. digronus n. sp. in the family Macrodasyidae, Acanthodasys flabellicaudus n. sp., Diplodasys sanctimariae n. sp., Tetranchyroderma hyponiglarum n. sp., T. korynetum n. sp. and T. oligopentancrum n. sp. in the family Thaumastodermatidae.